KONSEP TA’ĀWUN DALAM KRITIK TERHADAP PENETAPAN BATAS MAKSIMAL USIA KEPERSERTAAN PADA ASURANSI SYARIAH TA’ĀWUN - Riva Abdillah Aziz; Ending Solehudin (Asy-Syari'ah, 2022)
The purpose of this study is to review the concept of ta’āwun taught by Rasulullah Shalallahu Alaihi Wassalam and the reality of ta’āwun practice in the Islamic insurance industry in Indonesia. This research is also intended as a critique and input on the current practice of implementing ta’āwun. In contrast to conventional insurance, which uses a sale and purchase contract in its transactions, Sharia insurance uses the concept of ta’āwun in its transaction contracts. Qs. Al-Maidah verse 2 is the legal basis of this ta’āwun concept. This research used qualitative methods, the descriptive approach, and library research. The results of this study conclude that the concept of ta’āwun used by Islamic insurance currently needs to fully reflect the concept of ta’āwun in Qs Al-Maidah verse 2, which has been practised by Rasulullah Shalallahu Alaihi Wassalam and his friends. In practice, Sharia insurance companies set a maximum age limit for prospective participants, while the maximum age for participation is 65 years. This maximum age limit for participation means that not all prospective Sharia insurance participants can be accepted as customers. It is undoubtedly different from the practice of ta’āwun that existed at the time of Rasulullah Shalallahu Alaihi Wassalam, where the concept of ta’āwun was carried out without knowing the conditions. It is fitting for Sharia insurance to adhere to the principle of monotheism properly and rely on Allah Subhanallahu Wata'ala to carry out the wheels of its Sharia insurance business by not limiting participation age. Sharia insurance practitioners naturally adhere to the principles of ta’āwun and monotheism and believe with certainty that to worship Allah Subhanallahu wa Ta'ala, even though there is no age limit for participation, the company will still get the benefits expected in other ways.